The cause of damage and failure of the Mud-brick vault of the Khan in New-Gourna. (October 2021) - Szabó, Simon; Kövesdi, Andrea; Vasáros, Zsolt; Csicsely, Ágnes; Hegyi, Dezső
Highlights: Adobe masonry vaults. Failure of vaults. Mud architecture. Hassan Fathy. 3D FEM nonlinear analyis. Abstract: New Gourna, Egypt became an iconic place of mud-brick architecture in the middle of the 20th century as a result of the work of Hassan Fathy. In the dry climate of Egypt, mud-brick is an almost perfect building material, but the change in the environmental circumstances have caused damage to the structures. The present study aims to find the root of the problems to give chance to find suggestions for reliable strengthening. The paper focuses on one of the central buildings of New Gourna, the so-called Khan, designed by Hassan Fathy. The structure of the arcade of the Khan is modeled by advanced Finite Element method to simulate gradual deformation and failure with special attention to recent renovations that seem to have turned the condition of the structures even worse. As there are no experimental tests on the real materials, possible material models were collected for the analysis, and the most feasible result, which fits the visible failure was accepted. According to the analysis, the failure of the structure is caused by the wetting of the mud mortar layer between the limestone elements of the plinth. There were no significant signs of weakness in the foundation. The wetting of the mud mortar in the plinth is caused by the dramatical change in the ground-water level caused by the building of the Aswan High Dam and the dramatic change in the amount of wastewater caused by the increased population in New Gourna.